Preparation method of graphene oxide / nitrile rubber / sodium lignin sulfonate epoxy coating
By grafting nitrile rubber and sodium lignosulfonate onto graphene oxide, nano-graphene oxide/nitrile rubber/sodium lignosulfonate powder is formed, which solves the problem of poor dispersibility of graphene oxide in epoxy resin coatings and improves the corrosion resistance and mechanical properties of the coating.
Patent Information
- Application Number
- CN202311580291.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-24
- Publication Date
- 2025-10-28
- Estimated Expiration
- 2043-11-24
AI Technical Summary
Graphene oxide exhibits poor dispersion in epoxy resin coatings, resulting in insufficient corrosion resistance and mechanical properties of the coatings.
A high-temperature mechanochemical method was used to graft nitrile rubber and sodium lignosulfonate onto graphene oxide to form nano-graphene oxide/nitrile rubber/sodium lignosulfonate powder, which was then incorporated into a coating to form a coating layer through a simple application method.
It improves the corrosion resistance, mechanical properties, and thermodynamic properties of epoxy resin coatings, solves the problem of poor dispersion of graphene oxide in epoxy resin, and broadens the application fields of epoxy resin.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating preparation, specifically relating to a method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating. Background Technology
[0002] Epoxy resin, as an excellent thermosetting material, is widely used in anti-corrosion coatings in aerospace, petrochemical, and shipbuilding industries due to its low cost, strong adhesion, high density, and good corrosion resistance, thermal stability, and mechanical properties. However, the highly cross-linked structure of epoxy resin results in poor toughness and brittleness, and the high hydroxyl content in cured epoxy resin limits its applications.
[0003] Currently, there are two main methods for modifying epoxy resins: chemical and physical. Chemical methods involve introducing soft or hard chains onto epoxy groups or hydroxyl groups using chemical means, thereby improving the toughness and hardness of the epoxy resin. Physical methods involve introducing inorganic fillers to form organic-inorganic composite materials. Physical filler methods are used to address surface defects in composite materials, achieving purposes such as filling, leveling, protection, and insulation of the substrate. The filled epoxy resin coating can smooth, protect, and insulate the substrate by reducing surface defects.
[0004] Currently, various nanofillers are available, such as SiO2, TiO2, ZnO, CaCO3, SnO2, Fe3O4, graphene, graphene oxide (GO), carbon nanotubes, and boron (BN). Adding these nanofillers to epoxy resins can significantly improve their mechanical properties, corrosion resistance, weather resistance, and other special properties. Among them, graphene oxide (GO) is an ideal filler for epoxy resin modification due to its excellent properties. GO can not only fill the pores generated during epoxy resin curing, forming a "maze-like" physical barrier layer, but it can also transfer electrons from the matrix to the coating, thereby controlling the rate of electrochemical corrosion reactions and achieving cathodic protection. However, GO tends to aggregate in epoxy resins, resulting in poor dispersibility. Modifying GO utilizes the abundant functional groups on its surface to react with modifiers, achieving a modification effect and thus improving its compatibility with epoxy resins. This leads to better dispersibility of GO in epoxy resins, thereby improving the corrosion resistance of the coating. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating to solve the problem of poor dispersibility of GO in epoxy resin coatings.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating involves first grafting nitrile rubber and sodium lignosulfonate onto GO using a high-temperature mechanochemical method to modify GO; then filling the coating with graphene oxide / nitrile rubber / sodium lignosulfonate using a filler method; and finally applying the coating onto a substrate using a simple smearing method.
[0008] The preparation method specifically includes the following steps:
[0009] (1) Preparation of nanofillers
[0010] Weigh out graphene oxide, nitrile rubber, and sodium lignosulfonate according to the mass ratio, and then prepare nano-graphene oxide / nitrile rubber / sodium lignosulfonate by mechanochemical method: Mix graphene oxide, nitrile rubber, and sodium lignosulfonate evenly, and then ball mill the mixture. After ball milling, cool it to room temperature in the furnace. Take out the product, wash it, and dry it to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0011] (2) Substrate pretreatment
[0012] After cleaning the substrate with ethanol, it was ultrasonically cleaned in acetone solution, then rinsed with deionized water and dried, and finally sandblasted.
[0013] (3) The preparation of coatings includes film-forming substances, curing agents and nanofillers. The specific steps are as follows: after mixing the film-forming substances and nanofillers, ultrasonic stirring is performed under ice-water mixture, then curing agent is added and magnetic stirring is performed, and finally degassing is performed in vacuum.
[0014] (4) Coating treatment
[0015] Apply the coating liquid to the substrate using a coating stick, cure at room temperature, and repeat the application to obtain the coating.
[0016] in:
[0017] In step (1), the particle size of graphene oxide is 50-500 nm; the mass ratio of graphene oxide, nitrile rubber, and sodium lignosulfonate is 1:(0.5-4):(0.25-2).
[0018] In step (1), the ball milling process specifically involves: using argon gas as the milling atmosphere, and milling at 100-700℃ and a milling speed of 5-40 r / min for 8-24 hours.
[0019] In step (1), the powder is first cleaned with ethanol and then with distilled water; the drying temperature is 60-100℃ and the drying time is 24-48h.
[0020] In step (1), the particle size of the nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder is 10-500 nm.
[0021] In step (2), the ultrasonic cleaning time is 0.5-2 hours and the sandblasting angle is 40-60°.
[0022] In step (3), the film-forming substance is epoxy resin, acrylic acid and dimethyl silicone oil, the nanofiller is nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder, and the curing agent is 5034w phenolic amine; the mass ratio of epoxy resin, acrylic acid, dimethyl silicone oil, 5034w phenolic amine and nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder is (15-25):(0.5-2):(0.5-2):(2-10):(0.1-10); the epoxy resin is specifically bisphenol A diglycidyl ether.
[0023] In step (3), the ultrasonic stirring time is 10-30 min; the magnetic stirring speed is 100-1000 r / min and the time is 10-60 min; the vacuum degassing temperature is 25-40℃ and the time is 0.5-2 h.
[0024] In step (4), the application is repeated 2-5 times and the curing time is 3-8 hours.
[0025] The coating prepared by the method provided by the present invention has a thickness of 140-350 μm, a hardness ≥85 MPa, an adhesion strength ≥14 MPa, and an impact strength ≥53 kg·cm.
[0026] Compared with existing technologies, the method provided by this invention has the following advantages:
[0027] This coating, achieved by incorporating nano-graphene oxide / nitrile rubber / sodium lignosulfonate, effectively improves the corrosion resistance, mechanical properties, and thermodynamic properties of epoxy resin coatings. Furthermore, the preparation method is simple and inexpensive. Due to the modification of nitrile rubber and sodium lignosulfonate, GO's dispersibility in epoxy resin coatings is effectively improved, further enhancing the coating's corrosion resistance, mechanical properties, and thermodynamic properties. This solves the problem of poor GO dispersibility in epoxy resins, thereby significantly improving the performance of epoxy resin coatings and broadening the application fields of epoxy resins. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be noted that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0029] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods. The materials, reagents and instruments used are all conventional materials, reagents and instruments in the art and can be obtained by those skilled in the art through commercial channels.
[0030] Example 1
[0031] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating specifically includes the following steps:
[0032] (1) Mix 40g of GO with a particle size of 50nm, 40g of nitrile rubber and 20g of sodium lignosulfonate evenly, and add them to a ball mill jar. The ball-to-material ratio is 20:1 and the grinding bead particle size ratio is 16:12:8mm. The ball mill is carried out at a temperature of 300℃ and a ball milling speed of 40r / min for 8h. The ball milling atmosphere is argon. After the ball milling is completed, the furnace is cooled to room temperature. After the product is taken out, it is first washed with ethanol and then centrifuged. Then it is washed with distilled water and centrifuged again. After centrifugation, it is dried at 80℃ for 24h to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0033] (2) Cut 5083 aluminum alloy into 30mm×30mm×5mm aluminum alloy samples. After cleaning the substrate with ethanol, ultrasonically clean it in acetone solution for 0.5h. Then rinse it with deionized water and dry it. Finally, perform sandblasting treatment with a sandblasting pressure of 0.7-0.9MPa and a sandblasting angle of 40-60°.
[0034] (3) Mix 16g epoxy resin, 1.5g acrylic acid, 1g dimethyl silicone oil and 1g nano graphene oxide / nitrile rubber / sodium lignosulfonate and then ultrasonically stir in ice water mixture for 10min; then add 4g 5034w phenolic amine to the mixture and magnetically stir at 500r / min for 10min. After that, degas the mixture in vacuum at 25℃ for 0.5h.
[0035] (4) Apply the coating liquid to the substrate using a 70μm coating stick and cure at room temperature for 3.5h. Repeat the coating and curing process three times to obtain a coating with a thickness of about 210μm.
[0036] The coating obtained in this embodiment was characterized for performance.
[0037] 1. The coating of this embodiment was tested for impact, abrasion resistance, hardness, and adhesion. Its hardness reached 90 MPa, its adhesion strength reached 18 MPa, and its impact strength reached 62 kg·cm. The original coating had a hardness of 65 MPa, an adhesion strength of 11 MPa, and an impact strength of 50 kg·cm.
[0038] 2. Electrochemical testing of this embodiment showed that the coating was still in the initial stage of corrosion after immersion for 720 hours. Electrochemical testing of the original coating after immersion for 480 hours showed that the coating had entered the later stage of corrosion.
[0039] 3. Salt spray tests were conducted on the coating of this embodiment and the original coating. The coating of this embodiment underwent a cross-shaped salt spray test. After 600 hours of salt spray testing, a small amount of rust appeared on the surface of the coating, but no bubbles or peeling occurred. The original coating, after 600 hours of salt spray testing, showed a large amount of rust on its surface, and the coating swelled and showed signs of peeling.
[0040] Example 2
[0041] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating specifically includes the following steps:
[0042] (1) Mix 40g of GO with a particle size of 50nm, 20g of nitrile rubber and 10g of sodium lignosulfonate evenly, and add them to a ball mill jar. The ball-to-material ratio is 20:1 and the grinding ball particle size ratio is 16:12:8mm. The ball mill is carried out at a temperature of 300℃ and a ball milling speed of 40r / min for 8h. The ball milling atmosphere is argon. After the ball milling is completed, the furnace is cooled to room temperature. After the product is taken out, it is first washed with ethanol and then centrifuged. Then it is washed with distilled water and centrifuged again. After centrifugation, it is dried at 80℃ for 24h to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0043] (2) Cut 5083 aluminum alloy into 30mm×30mm×5mm aluminum alloy samples. After cleaning the substrate with ethanol, ultrasonically clean it in acetone solution for 0.5h. Then rinse it with deionized water and dry it. Finally, perform sandblasting treatment with a sandblasting pressure of 0.7-0.9MPa and a sandblasting angle of 40-60°.
[0044] (3) Mix 16g epoxy resin, 1.5g acrylic acid, 1g dimethyl silicone oil and 1g nano graphene oxide / nitrile rubber / sodium lignosulfonate and then ultrasonically stir in ice water mixture for 10min; then add 4g 5034w phenolic amine to the mixture and magnetically stir at 500r / min for 10min. After that, degas the mixture in vacuum at 25℃ for 0.5h.
[0045] (4) Apply the coating liquid to the substrate using a 70μm coating stick and cure at room temperature for 3.5h. Repeat the coating and curing process three times to obtain a coating with a thickness of about 210μm.
[0046] The coating obtained in this embodiment was characterized for performance.
[0047] 1. The coating of this embodiment was tested for impact, wear resistance, hardness and adhesion. Its hardness can reach 88MPa, its adhesion strength can reach 16MPa and its impact strength can reach 60kg·cm.
[0048] 2. Electrochemical tests were performed on this embodiment. After immersion for 600 hours, the coating was still in the initial stage of corrosion. After immersion for 720 hours, the coating was still in the intermediate stage of corrosion.
[0049] 3. Salt spray tests were conducted on this embodiment and the original coating. The coating in this embodiment underwent a cross-shaped salt spray test for 480 hours, during which no rust, bubbles, or peeling were observed on the surface. However, after 600 hours of salt spray testing, rust and bubbles appeared on the coating surface.
[0050] Example 3
[0051] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating specifically includes the following steps:
[0052] (1) Mix 40g of GO with a particle size of 50nm, 40g of nitrile rubber and 20g of sodium lignosulfonate evenly, and add them to a ball mill jar. The ball-to-material ratio is 10:1 and the grinding ball particle size ratio is 16:12:8mm. The ball mill is carried out at a temperature of 300℃ and a ball milling speed of 40r / min for 8h. The ball milling atmosphere is argon. After the ball milling is completed, the furnace is cooled to room temperature. After the product is taken out, it is first washed with ethanol and then centrifuged. Then it is washed with distilled water and centrifuged again. After centrifugation, it is dried at 80℃ for 24h to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0053] (2) Cut 5083 aluminum alloy into 30mm×30mm×5mm aluminum alloy samples. After cleaning the substrate with ethanol, ultrasonically clean it in acetone solution for 0.5h. Then rinse it with deionized water and dry it. Finally, perform sandblasting treatment with a sandblasting pressure of 0.7-0.9MPa and a sandblasting angle of 40-60°.
[0054] (3) Mix 16g epoxy resin, 1.5g acrylic acid, 1g dimethyl silicone oil and 1g nano graphene oxide / nitrile rubber / sodium lignosulfonate and then ultrasonically stir in ice water mixture for 10min; then add 4g 5034w phenolic amine to the mixture and magnetically stir at 500r / min for 10min. After that, degas the mixture in vacuum at 25℃ for 0.5h.
[0055] (4) Apply the coating liquid to the substrate using a 70μm coating stick and cure at room temperature for 3.5h. Repeat the coating and curing process three times to obtain a coating with a thickness of about 210μm.
[0056] The coating obtained in this embodiment was characterized for performance.
[0057] 1. The coating of this embodiment was tested for impact, wear resistance, hardness and adhesion. Its hardness can reach 87MPa, its adhesion strength can reach 17MPa and its impact strength can reach 57kg·cm.
[0058] 2. Electrochemical tests were performed on this embodiment. After immersion for 600 hours, the coating was still in the initial stage of corrosion. After immersion for 720 hours, the coating was still in the intermediate stage of corrosion.
[0059] 3. Salt spray tests were conducted on this embodiment and the original coating. The coating in this embodiment underwent a cross-shaped salt spray test. After 480 hours of salt spray, no rust, bubbles, or peeling were observed on the surface. After 600 hours of salt spray, rust and bubbles appeared on the coating surface, but no peeling occurred.
[0060] Example 4
[0061] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating specifically includes the following steps:
[0062] (1) Mix 40g of GO with a particle size of 50nm, 40g of nitrile rubber and 20g of sodium lignosulfonate evenly, and add them to a ball mill jar. The ball-to-material ratio is 20:1 and the grinding ball particle size ratio is 16:12:8mm. The ball mill is carried out at a temperature of 500℃ and a ball milling speed of 40r / min for 8h. The ball milling atmosphere is argon. After the ball milling is completed, the furnace is cooled to room temperature. After the product is taken out, it is first washed with ethanol and then centrifuged. Then it is washed with distilled water and centrifuged again. After centrifugation, it is dried at 80℃ for 24h to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0063] (2) Cut 5083 aluminum alloy into 30mm×30mm×5mm aluminum alloy samples. After cleaning the substrate with ethanol, ultrasonically clean it in acetone solution for 0.5h. Then rinse it with deionized water and dry it. Finally, perform sandblasting treatment with a sandblasting pressure of 0.7-0.9MPa and a sandblasting angle of 40-60°.
[0064] (3) Mix 16g epoxy resin, 1.5g acrylic acid, 1g dimethyl silicone oil and 1g nano graphene oxide / nitrile rubber / sodium lignosulfonate and then ultrasonically stir in ice water mixture for 10min; then add 4g 5034w phenolic amine to the mixture and magnetically stir at 500r / min for 10min. After that, degas the mixture in vacuum at 25℃ for 0.5h.
[0065] (4) Apply the coating liquid to the substrate using a 70μm coating stick and cure at room temperature for 3.5h. Repeat the coating and curing process three times to obtain a coating with a thickness of about 210μm.
[0066] The structure and properties of the coating obtained in this embodiment were characterized.
[0067] 1. The coating of this embodiment was tested for impact, wear resistance, hardness and adhesion. Its hardness can reach 92MPa, its adhesion strength can reach 20MPa and its impact strength can reach 64kg·cm.
[0068] 2. Electrochemical tests were performed on this embodiment. After immersion for 840 hours, the coating was still in the initial stage of corrosion. After immersion for 960 hours, the coating was in the intermediate stage of corrosion.
[0069] 3. Salt spray tests were conducted on this embodiment and the original coating. The coating in this embodiment underwent a cross-shaped salt spray test. After 840 hours of salt spray, no rust, bubbles, or peeling were observed on the surface. After 960 hours of salt spray, rust appeared on the surface.
[0070] Example 5
[0071] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating specifically includes the following steps:
[0072] (1) Mix 40g of GO with a particle size of 50nm, 40g of nitrile rubber and 20g of sodium lignosulfonate evenly, and add them to a ball mill jar. The ball-to-material ratio is 20:1 and the grinding ball particle size ratio is 16:12:8mm. The ball mill is carried out at a temperature of 700℃ and a ball milling speed of 40r / min for 8h. The ball milling atmosphere is argon. After the ball milling is completed, the furnace is cooled to room temperature. After the product is taken out, it is first washed with ethanol and then centrifuged. Then it is washed with distilled water and centrifuged again. After centrifugation, it is dried at 80℃ for 24h to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0073] (2) Cut 5083 aluminum alloy into 30mm×30mm×5mm aluminum alloy samples. After cleaning the substrate with ethanol, ultrasonically clean it in acetone solution for 0.5h. Then rinse it with deionized water and dry it. Finally, perform sandblasting treatment with a sandblasting pressure of 0.7-0.9MPa and a sandblasting angle of 40-60°.
[0074] (3) Mix 16g epoxy resin, 1.5g acrylic acid, 1g dimethyl silicone oil and 1g nano graphene oxide / nitrile rubber / sodium lignosulfonate and then ultrasonically stir in ice water mixture for 10min; then add 4g 5034w phenolic amine to the mixture and magnetically stir at 500r / min for 10min. After that, degas the mixture in vacuum at 25℃ for 0.5h.
[0075] (4) Apply the coating liquid to the substrate using a 70μm coating stick and cure at room temperature for 3.5h. Then repeat the coating and curing process three times to obtain a coating with a thickness of about 210μm.
[0076] The coating obtained in this embodiment was characterized for performance.
[0077] 1. The coating of this embodiment was tested for impact, wear resistance, hardness and adhesion. Its hardness can reach 89MPa, its adhesion strength can reach 15MPa and its impact strength can reach 56kg·cm.
[0078] 2. Electrochemical tests were performed on this embodiment. After immersion for 600 hours, the coating was still in the initial stage of corrosion. After immersion for 720 hours, the coating was still in the intermediate stage of corrosion.
[0079] 3. Salt spray tests were conducted on the coating of this embodiment and the original coating. The coating of this embodiment was subjected to a "cross" scratch salt spray test. After 480 hours of salt spray test, no rust, bubbles or peeling were observed on the surface of the coating of this embodiment. However, after 600 hours of salt spray test, rust and bubbles were observed on the surface.
[0080] Example 6
[0081] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating specifically includes the following steps:
[0082] (1) Mix 40g of GO with a particle size of 50nm, 40g of nitrile rubber and 20g of sodium lignosulfonate evenly, and add them into a ball mill jar. The ball-to-material ratio is 20:1 and the grinding bead particle size ratio is 16:12:8mm. The ball mill is carried out at a temperature of 500℃ and a ball milling speed of 10r / min for 8h. The ball milling atmosphere is argon. After the ball milling is completed, the furnace is cooled to room temperature. After the product is taken out, it is first washed with ethanol and then centrifuged. Then it is washed with distilled water and centrifuged again. After centrifugation, it is dried at 80℃ for 24h to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0083] (2) Cut 5083 aluminum alloy into 30mm×30mm×5mm aluminum alloy samples. After cleaning the substrate with ethanol, ultrasonically clean it in acetone solution for 0.5h. Then rinse it with deionized water and dry it. Finally, perform sandblasting treatment with a sandblasting pressure of 0.7-0.9MPa and a sandblasting angle of 40-60°.
[0084] (3) Mix 16g epoxy resin, 1.5g acrylic acid, 1g dimethyl silicone oil and 1g nano graphene oxide / nitrile rubber / sodium lignosulfonate and then ultrasonically stir in ice water mixture for 10min; then add 4g 5034w phenolic amine to the mixture and magnetically stir at 500r / min for 10min. After that, degas the mixture in vacuum at 25℃ for 0.5h.
[0085] (4) Apply the coating liquid to the substrate using a 70μm coating stick and cure at room temperature for 3.5h. Then repeat the coating and curing process three times to obtain a coating with a thickness of about 210μm.
[0086] The coating obtained in this embodiment was characterized for performance.
[0087] 1. The coating of this embodiment was tested for impact, wear resistance, hardness and adhesion. Its hardness can reach 86MPa, its adhesion strength can reach 14MPa and its impact strength can reach 53kg·cm.
[0088] 2. Electrochemical tests were performed on this embodiment. After immersion for 480 hours, the coating was still in the initial stage of corrosion. After immersion for 600 hours, the coating was still in the intermediate stage of corrosion.
[0089] 3. Salt spray tests were conducted on the coating of this embodiment and the original coating. The coating of this embodiment was subjected to a "cross" scratch salt spray test. After immersion in the salt spray test for 480 hours, no rust, bubbles or peeling were observed on the surface of the coating. However, after 600 hours of salt spray test, a large amount of rust and bubbles appeared on the surface of the coating, and the surface also showed signs of peeling.
[0090] Example 7
[0091] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating specifically includes the following steps:
[0092] (1) Mix 40g of GO with a particle size of 50nm, 40g of nitrile rubber and 20g of sodium lignosulfonate evenly, and add them to a ball mill jar. The ball-to-material ratio is 20:1 and the grinding ball particle size ratio is 16:12:8mm. The ball mill is carried out at a temperature of 500℃ and a ball milling speed of 40r / min for 16h. The ball milling atmosphere is argon. After the ball milling is completed, the furnace is cooled to room temperature. After the product is taken out, it is first washed with ethanol and then centrifuged. Then it is washed with distilled water and centrifuged again. After centrifugation, it is dried at 80℃ for 24h to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0093] (2) Cut 5083 aluminum alloy into 30mm×30mm×5mm aluminum alloy samples. After cleaning the substrate with ethanol, ultrasonically clean it in acetone solution for 0.5h. Then rinse it with deionized water and dry it. Finally, perform sandblasting treatment with a sandblasting pressure of 0.7-0.9MPa and a sandblasting angle of 40-60°.
[0094] (3) Mix 16g epoxy resin, 1.5g acrylic acid, 1g dimethyl silicone oil and 1g nano graphene oxide / nitrile rubber / sodium lignosulfonate and then ultrasonically stir in ice water mixture for 10min; then add 4g 5034w phenolic amine to the mixture and magnetically stir at 500r / min for 10min. After that, degas the mixture in vacuum at 25℃ for 0.5h.
[0095] (4) Apply the coating liquid to the substrate using a 70μm coating stick and cure at room temperature for 3.5h. Then repeat the coating and curing process three times to obtain a coating with a thickness of about 210μm.
[0096] The coating obtained in this embodiment was characterized for performance.
[0097] 1. The coating of this embodiment was tested for impact, wear resistance, hardness and adhesion. Its hardness can reach 91MPa, its adhesion strength can reach 18MPa and its impact strength can reach 61kg·cm.
[0098] 2. Electrochemical tests were performed on this embodiment. After immersion for 720 hours, the coating was still in the initial stage of corrosion. After immersion for 840 hours, the coating was still in the intermediate stage of corrosion.
[0099] 3. Salt spray tests were conducted on the coating of this embodiment and the original coating. The coating of this embodiment underwent a cross-shaped salt spray test. After 720 hours of salt spray test, no rust, bubbles, or peeling were observed on the surface of the coating. However, after 840 hours of salt spray test, rust appeared on the surface of the coating, but there were no obvious bubbles or peeling.
[0100] Example 8
[0101] A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating specifically includes the following steps:
[0102] (1) Mix 40g of GO with a particle size of 50nm, 40g of nitrile rubber and 20g of sodium lignosulfonate evenly, and add them to a ball mill jar. The ball-to-material ratio is 20:1 and the grinding ball particle size ratio is 16:12:8mm. The ball mill is carried out at a temperature of 500℃ and a ball milling speed of 40r / min for 16h. The ball milling atmosphere is argon. After the ball milling is completed, the furnace is cooled to room temperature. After the product is taken out, it is first washed with ethanol and then centrifuged. Then it is washed with distilled water and centrifuged again. After centrifugation, it is dried at 80℃ for 24h to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder.
[0103] (2) Cut 5083 aluminum alloy into 30mm×30mm×5mm aluminum alloy samples. After cleaning the substrate with ethanol, ultrasonically clean it in acetone solution for 0.5h. Then rinse it with deionized water and dry it. Finally, perform sandblasting treatment with a sandblasting pressure of 0.7-0.9MPa and a sandblasting angle of 40-60°.
[0104] (3) Mix 16g epoxy resin, 1.5g acrylic acid, 1g dimethyl silicone oil and 5g nano graphene oxide / nitrile rubber / sodium lignosulfonate and ultrasonically stir for 10min in ice water mixture; then add 4g 5034w phenolic amine to the mixture and magnetically stir at 500r / min for 10min. After that, degas the mixture in a vacuum at 25℃ for 0.5h.
[0105] (4) Apply the coating liquid to the substrate using a 70μm coating stick and cure at room temperature for 3.5h. Then repeat the coating and curing process three times to obtain a coating with a thickness of about 210μm.
[0106] The structure and properties of the coating obtained in this embodiment were characterized.
[0107] 1. The coating of this embodiment was tested for impact, wear resistance, hardness and adhesion. Its hardness can reach 86MPa, its adhesion strength can reach 15MPa and its impact strength can reach 54kg·cm.
[0108] 2. Electrochemical tests were performed on this embodiment. After immersion for 600 hours, the coating was still in the initial stage of corrosion. After immersion for 720 hours, the coating was still in the intermediate stage of corrosion.
[0109] 3. Salt spray tests were conducted on the coating of this embodiment and the original coating. The coating of this embodiment was subjected to a "cross" scratch salt spray test. After 480 hours of salt spray test, no rust, bubbles, or peeling were observed on the surface of the coating. However, after 600 hours of salt spray test, rust appeared on the surface of the coating.
[0110] Comparative Example 1
[0111] The difference is that 1g of unmodified GO is added to the coating.
[0112] The coating of this comparative example was tested for impact resistance, abrasion resistance, hardness, and adhesion. Its hardness was 80 MPa, adhesion strength was 12 MPa, and impact strength was 48 kg·cm. Electrochemical testing of this comparative example showed that the coating had entered the later stage after immersion for 600 hours. Salt spray testing of this comparative example showed that after 720 hours of "cross-scratch" salt spray, rust, bubbles, and peeling began to appear on the coating. This is because the unmodified GO agglomerates in the coating, leading to a deterioration in its performance.
[0113] Comparative Example 2
[0114] Same as Example 1, except that the amount of nano-graphene oxide / nitrile rubber / sodium lignosulfonate added is 5g.
[0115] The coating of this comparative example was tested for impact resistance, abrasion resistance, hardness, and adhesion. Its hardness was 88 MPa, adhesion strength was 14 MPa, and impact strength was 50 kg·cm. Electrochemical testing of this comparative example showed that the coating had entered the mid-stage after immersion for 720 h. Salt spray testing of this comparative example showed that after 800 h of "cross-scratch" salt spray, rust, bubbles, and peeling began to appear on the coating. This is because the addition of excessive modified GO causes aggregation.
[0116] Comparative Example 3
[0117] Same as Example 1, except that the ball milling time is 4 hours.
[0118] The coating of this comparative example was tested for impact, abrasion resistance, hardness, and adhesion. Its hardness was 79 MPa, adhesion strength was 11 MPa, and impact strength was 48 kg·cm. Electrochemical testing of this comparative example showed that the coating had entered the later stage after immersion for 600 hours. Salt spray testing of this comparative example showed that after 600 hours of "cross-scratch" salt spray testing, rust, bubbles, and peeling began to appear on the coating. This is because the ball milling time was too short, and the nitrile rubber and sodium lignosulfonate were not grafted onto the GO, causing the GO to agglomerate in the coating.
[0119] Comparative Example 4
[0120] Same as Example 1, except that the ball milling temperature is 100°C.
[0121] The coating of this comparative example was tested for impact resistance, abrasion resistance, hardness, and adhesion. Its hardness was 78 MPa, adhesion strength was 11 MPa, and impact strength was 47 kg·cm. Electrochemical testing of this comparative example showed that the coating had entered the later stage after immersion for 500 hours. Salt spray testing of this comparative example showed that after 480 hours of "cross-scratch" salt spray, rust, bubbles, and peeling began to appear on the coating. This is because the ball milling temperature was too low, and the nitrile rubber and sodium lignosulfonate were not grafted onto the GO, causing GO to agglomerate in the coating.
[0122] The above description is merely a preferred embodiment of the invention. Given that those skilled in the art can make appropriate changes and modifications to the above embodiments, the present invention is not limited to the specific embodiments described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating, characterized in that, Specifically, the following steps are included: (1) Preparation of nanofillers: Weigh out graphene oxide, nitrile rubber, and sodium lignosulfonate in a mass ratio of 1:(0.5-1):(0.25-0.5). Then, prepare nano-graphene oxide / nitrile rubber / sodium lignosulfonate using a mechanochemical method: Mix graphene oxide, nitrile rubber, and sodium lignosulfonate evenly, and then ball mill the mixture under an argon atmosphere at 100-700℃ and a ball milling speed of 5-40 r / min for 8-24 h. After ball milling, cool to room temperature in the furnace. After removing the product, clean and dry it to obtain nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder. (2) Substrate pretreatment: After cleaning the substrate with ethanol, it was ultrasonically cleaned in acetone solution, then rinsed with deionized water and dried, and finally sandblasted. (3) Preparation of coatings: After mixing the film-forming material with the nanofiller, the mixture was ultrasonically stirred in an ice-water mixture, followed by the addition of a curing agent and magnetic stirring, and finally degassing in a vacuum. The film-forming substance is epoxy resin, acrylic acid and dimethyl silicone oil, the nanofiller is nano graphene oxide / nitrile rubber / sodium lignosulfonate powder, and the curing agent is 5034 w phenolic amine; The mass ratio of the epoxy resin, acrylic acid, dimethyl silicone oil, 5034 w phenolic amine, and nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder is (15-25):(0.5-2):(0.5-2):(2-10):(0.1-10). The epoxy resin is diglycidyl ether of bisphenol A; (4) Application treatment: Apply the coating liquid to the substrate using a coating stick, cure at room temperature, and repeat the application to obtain the coating.
2. The method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating according to claim 1, characterized in that, In step (1), the particle size of graphene oxide is 50-500 nm.
3. The method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating according to claim 1, characterized in that, In step (1), the powder is first cleaned with ethanol and then with distilled water; the drying temperature is 60-100℃ and the drying time is 24-48 h.
4. The method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating according to claim 1, characterized in that, In step (1), the particle size of the nano-graphene oxide / nitrile rubber / sodium lignosulfonate powder is 10-500 nm.
5. The method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating according to claim 1, characterized in that, In step (2), the ultrasonic cleaning time is 0.5-2 h and the sandblasting angle is 40-60°.
6. The method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating according to claim 1, characterized in that, In step (3), the ultrasonic stirring time is 10-30 min; the magnetic stirring speed is 100-1000 r / min and the time is 10-60 min; the vacuum degassing temperature is 25-40℃ and the time is 0.5-2 h.
7. The method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating according to claim 1, characterized in that, In step (4), the application is repeated 2-5 times and the curing time is 3-8 hours.
8. The method for preparing a graphene oxide / nitrile rubber / sodium lignosulfonate epoxy coating according to claim 1, characterized in that, The resulting coating has a thickness of 140-350 μm, a hardness of ≥85 MPa, an adhesion strength of ≥14 MPa, and an impact strength of ≥53 kg·cm.
Citation Information
Patent Citations
Sulfonic group modified graphene, and preparation method and application thereof in water-based epoxy coating
CN110655071A
Preparation method of modified graphene oxide epoxy composite anticorrosive coating
CN112662270A
Graphene oxide slurry as well as preparation method and application thereof
CN113789076A